Artificial electrode interfaces enable stable operation of freestanding anodes for high-performance flexible lithium ion batteries. Issue 23 (29th May 2019) - Liu, Lixiang; Zhu, Minshen; Huang, Shaozhuan; Lu, Xueyi; Zhang, Long; Li, Yang; Wang, Sitao; Liu, Lifeng; Weng, Qunhong; Schmidt, Oliver G.
Abstract : Artificial electrode interfaces enable stable operation of freestanding electrodes with high energy output and mechanical robustness. Abstract : High-performance flexible lithium-ion batteries are leading candidates for power sources of wearable and foldable electronics. As a result, it is vital to design freestanding electrodes with high capacity and stability. Herein, we develop a novel strategy to significantly improve the performance of freestanding anodes by artificially introducing an ultrathin but robust interface based on polyacrylamide/gelatin gel with excellent mechanical durability and ionic conductivity. The artificial interface suppresses the formation of a thick solid electrolyte interface, facilitates charge transfer processes and strengthens the integrity of the electrode. Benefitting from these merits, our freestanding anode made of the nano/microstructured NiFe2 O4 –CNTs composite achieves a high capacity of 612 mA h g −1 based on the total mass of the electrode. The high-performance freestanding anode further enables a stable output capacity of 140 mA h g −1 over 1000 charge/discharge cycles for a full battery using commercial LiMn2 O4 as the cathode material. Meanwhile, the excellent rate performance of the freestanding anode guarantees high energy output up to 255 W h kg −1 at a high power density of 12 000 W kg −1 for the full battery. Moreover, the intrinsic flexibility of the freestanding electrodes enables the fabrication of a flexible lithium-ion battery, which is highly stable even under harsh mechanical deformation. This work provides a new perspective to fabricate next-generation flexible batteries with high energy density and excellent stability, further advancing the development of foldable and wearable electronics toward practical applications.